2008
DOI: 10.1007/s10803-008-0560-z
|View full text |Cite
|
Sign up to set email alerts
|

Child Temperaments, Differential Parenting, and the Sibling Relationships of Children with Autism Spectrum Disorder

Abstract: This study examined associations between sibling temperaments, differential parenting, and the quality of the relationships between 50 children with autism spectrum disorder (ASD) and their typically developing siblings. The temperament dimension of persistence, but not activity level or emotional intensity, was found to relate to the quality of the sibling relationship. Effects were stronger for temperaments of the typically developing siblings, but persistence levels of both groups of children interacted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…It is, however, not clear whether these specific differences in parenting cognitions are the result of the impact of a child with ASD or whether these differences also exist in families with TD children only. In general parenting research there is evidence of differential parental treatment and differentiation in parenting cognitions within families (e.g., DeaterDeckard et al, 2005;Dunn, Plomin, & Daniels, 1986;Rivers & Stoneman, 2008), but no studies have explicitly focused on mother's differentiation in parenting cognitions within ASD families nor on variation in the degree of parental differentiation between ASD and TD families.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, not clear whether these specific differences in parenting cognitions are the result of the impact of a child with ASD or whether these differences also exist in families with TD children only. In general parenting research there is evidence of differential parental treatment and differentiation in parenting cognitions within families (e.g., DeaterDeckard et al, 2005;Dunn, Plomin, & Daniels, 1986;Rivers & Stoneman, 2008), but no studies have explicitly focused on mother's differentiation in parenting cognitions within ASD families nor on variation in the degree of parental differentiation between ASD and TD families.…”
Section: Discussionmentioning
confidence: 99%
“…For parents of ASD children, the majority of studies have explored children's characteristics (mainly core features of ASD) as a determinant of parenting stress or parental coping strategies (e.g., Firth & Dryer, 2013;Peters-Scheffer, Didden, & Korzilius, 2012 Van Leeuwen, & De Clercq, 2011, Nader-Grosbois & Mazzone, 2014Rivers & Stoneman, 2008). These significant differences in factors of personality may cause variations in parental behaviours, and notably ERSBs.…”
Section: Why It Is Relevant To Explore the Variability Of Parentalmentioning
confidence: 99%
“…In their interactions with each other, siblings may acquire many social and cognitive skills that are central to healthy social development (Furman and Buhrmester 1985). Travis and Sigman (1998) suggested that siblings may be especially important for children with autism because they provide opportunities to socially interact with other children under maximally supportive conditions (Rivers and Stoneman 2008). Research suggests that children with ASDs need exposure to typically developing children to gain experience and learn about proper social interaction and relationships (Knott et al1995;Tsao and Odom 2006).…”
Section: Sibling Relationshipsmentioning
confidence: 99%
“…, Boer 1990;Brody and Stoneman 1987;Bryany andCrockenberg 1980, Dunn andPlomin 1990) and even for siblings of children with disabilities (McHale and Gamble 1989). When siblings are dissatisfied with differential parenting, the quality of the sibling relationship suffers (Rivers and Stoneman 2008). It is not simply a matter of poor sibling relationships and parental favoring that lead to increased psychological difficulties, but it is a more complex issue involving children who are sensitive to changes in the wider sibling context (Richmond et al 2005;Schuntermann 2007).…”
Section: Parentingmentioning
confidence: 99%